Analisis Peluang dan Ancaman Perdagangan Internasional Indonesia pada Komoditas Peternakan (Susu) Tahun 2025 - Latifatunnisa Latifatunnisa (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the opportunities and threats facing Indonesia’s international trade in livestock commodities, particularly milk and dairy products. Indonesia is a country with steadily rising milk consumption, yet domestic production has not been able to meet this demand. Data indicates that more than 70% of the national milk demand is still met through imports. Indonesia’s main milk suppliers include New Zealand, the United States, and Australia. The research method employed is descriptive, utilizing both quantitative and qualitative approaches with data from the Central Statistics Agency (BPS), the FAO, and the USDA. The results of the study indicate that Indonesia has significant opportunities for the development of its domestic dairy industry, but faces various threats such as import dependency, global price fluctuations, and low domestic livestock productivity.